Evaluating the efficiency of horizontal drains on the stability of Earth Dam front face under rapid discharge conditions (case study: of Al- Houiz Dam - Jableh Lattakia) - لطف , محمد; عز الدين حسن , (Latakia University Journal -Engineering Sciences Series, 2022)
This research deals with the study of the stability of the upstream slope dam of Al- Houiz dam in the steady state and upon the rapid drawdown of the reservoir in its current condition, and while instating horizontal drains within this slope. The study included the deduction of safety factors in the theory of “Finite Element Method (FEM)” according to the GeoStudio-SLOPE/W, by connecting to the GeoStudio-SEEP/W, as well as the experimental deduction of safety factors according to the method of ordinary slices in order to cross-examine the results. we have developed three models to study the stability slope of the upstream. The first model is of dam in its current condition. The second one of constructing two horizontal drains, and the third of the construction of three horizontal drains. Having studied and analyzed the first model, we found that the safety factor in the current situation amounted to Fs = 2.597 in the steady state, reaching Fs = 0.966 at the unstable state (rapid drawdown), and based on the instability, we proposed the establishment of horizontal drains to evaluate their impact on the stability of the upstream slope of Al- Houiz dam. Thus it caused instability of the slope at the rapid drawdown. Having examined the stability during rapid drawdown in the second model, the safety factor was Fs = 1.680, and in the third model the safety factor was Fs = 1.982. Therefore, the installation of horizontal drains within the upstream slope of the earth dams contributes to increasing their stability during rapid drawdown.